How to present an informative summary of findings table for systematic reviews of interventions: A tutorial - Hilgart, Jennifer; Miles, Clare; Chase, Jo‐Ana (Cochrane evidence synthesis and methods, 2024)
This tutorial provides guidance on creating clear and informative summary of findings tables for systematic reviews of interventions. This tutorial provides guidance on creating clear and informative summary of findings tables for systematic reviews of interventions. We will explain what information is required in the different sections of the table. In the accompanying micro‐learning module, you can test your knowledge of the key components of a summary of findings table and practice calculating absolute risks. Summary of findings table micro learning module